Endophytic fungi from medicinal plant Garcinia cowa Roxb. ex Choisy and their antibacterial activity - Dian Handayani, Rezki Irvan Muslim, Nova Syafni, Muh. Ade Artasasta, Riga Riga (Journal of Applied Pharmaceutical Science, 2024)
Endophytic fungi grow inside plant tissues and produce biologically active substances without harming the host plant. Endophytic fungi isolated from the roots, barks, and leaves of Garcinia cowa Roxb. ex Choisy, an ethnomedicinal plant commonly used in West Sumatera, Indonesia, are the focus of this research, which aims to evaluate their antibacterial activity. Traditional medicine has made extensive use of this plant’s various parts. In total, 14 endophytic fungal isolates were obtained from plant fragments of G. cowa that had undergone surface sterilization. After four to six weeks of cultivation in rice medium, the fungus isolate was extracted with ethyl acetate (EtOAc). Each EtOAc extract of fungus was tested for antimicrobial activity using Kirby–Bauer diffusion against Staphylococcus aureus, Escherichia coli, Methicillin Resistant S. aureus, and Candida albicans. The measurement results of the inhibition zone indicate that the GCA3 isolate of endophytic fungi exhibited significant inhibitory diameters and demonstrated potential as an antibacterial agent. The GCA3 strain showed an inhibition diameter zone of 15.05 } 0.51 mm against S. aureus, 14.68 } 0.5 mm against E. coli, and 13.48 } 0.15 mm against MRSA. None of the fungi extracts can inhibit the growth of C. albicans. The fungus GCA3 has been determined to be identical to Penicillium citrinum through macroscopic, microscopic, and molecular identification methods. The findings indicate that endophytic fungi from the Garcinia plant can generate antibacterial compounds. Hence, additional investigation is required to separate these bioactive compounds.
Keywords: Medicinal plant, endophytic fungi, Penicillium citrinum